The Influence of Formation of Mechanical Skills and Numerical Literacy Skills on Welding Practicum of Problem Based Learning Model on Mechanical Engineering Education Study Program Students - Rohmanudin, Rohmanudin; Sutadji, Eddy; Dardiri, Ahmad (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2022)
This study was to determine the effect of machining skills and numeracy literacy skills formation on PBL model welding practicum for Mechanical Engineering Education Study Program students in the year 2016 and 2017. The method of this research approach was quantitative with path analysis. This study used a random sampling technique. The results showed that (1) the machining skills formation significantly influenced the PBL model welding practicum; and (2) the numeracy literacy skills formation significantly influences the PBL model welding practicum for students. The numeracy literacy skills test results have the most influence on the PBL model welding practicum for students